The big, the bad, and the dangerous: public perceptions and terrorism. Issue 1 (2nd January 2018) - Avdan, Nazli; Webb, Clayton
Abstract: Does coordination affect threat perceptions? The attacks in Paris and Brussels in 2015 and 2016 received a significant amount of attention in the media. The attacks were transnational, fatal, and perpetrated by the same group in western European countries. We argue that these are not the only features of the attacks that matter. The attacks involved coordination among teams of militants. This coordination signals sophistication. Sophistication amplifies threat perceptions independent of group reputation, fatality rate, or target location because sophistication suggests a greater capability to inflict harm. We provide experimental evidence of the relationship between coordination and threat perceptions. Our results contribute to a growing literature looking at the features of terrorist attacks and public perceptions of terrorism, and lay the groundwork for future research on the political and security consequences of coordinated terrorist attacks.